A study of the professional aspirations of graduate teachers - Wijetunga, S. (My University, 1983)
Teachers make a most important and tangible cotribution toward the quality of teaching and learning that takes place in classrooms. The state of ateacher's mental health is one indicator of how well he/she would perform in the classroom. The career needs and aspirations of teachers are closely linked up with their contentment or otherwise; a more contented teacher is one...